Tolerance to high temperatures in tadpoles of Leptodactylus fuscus and Hyla fuscovaria in temporary ponds (Amphibia, Leptodactylidae, Hylidae) - Abe, Augusto Shinya [UNESP]; Neto, J. R. [UNESP] (My University, 1991)
In temporary ponds tadpoles of the frogs Leptodactylus fuscus and Hyla fuscovaria may be exposed to temperatures up to 40-44°C. Experimental exposure to high temperature revealed survivals after 30 min at 42°C for H. fuscovaria and at 44°C for L. fuscus. -from Authors
Keywords: tadpole; temperature; temporary pond; Hyla fuscovaria; Hylidae; Leptodactylidae; Leptodactylus fuscus